Th e Enigma of US Productivity Slowdown: A Theoretical Analysis - Awan, Abdul Ghafoor; Khan, Rana Ejaz Ali (American Journal of Trade and Policy, 2014)
Introduction: The economy of the United States is the number one economy of the world on the basis of its GDP size. Many economies of the world depend upon the working upon it. However, US economy has been facing the phenomena of labour productivity slowdown since 1973. The productivity grow was witnessed during 1990s decade due to revolution of information technology but it was proved transitory. To investigate this phenomenon the economists have been actively working and using different theoretical and empirical approaches. But it is still an enigma and its real cause has so far not been detected. The objective of the Study: The objective of this research study is to investigate why US economy has been facing productivity growth slowdown since long, what are its causes and what is its possible solution?. Methodology: The author has used qualitative research approach in which real economy sector and technology economy sector have been studied on the basis of secondary data collected from OECD, IMF, World Bank,etc. The individual share of these sectors in the US GDP has been determined to analyze their effects on productivity growth. The author has also compared goods and services sectors and their contribution into the US GDP. Findings: The results of study shows that no breakthrough or major innovation has occurred in the major sector of US economy. Information technology is a small sector and growth in this sector during 1990s has not brought any signiﬁ cant impact on the US economy. The evidence shows that quality of patents is falling despite increasing number of researchers during the period of 1990-2010 and it reﬂ ects diminishing return on R&D investment in the technology sector. The ratio of input/output is 40/100 which is totally against the concept of constant return to scale.